Influence of preoperative information support on anxiety, pain and satisfaction with postoperative analgesia in children and adolescents after thoracic surgery: A randomized double blind study - Tomaszek, Lucyna; Cepuch, Grazyna; Fenikowski, Dariusz (Biomedical papers, 2019)
Aims/Background. The proportion of patients who experience anxiety prior to planned surgery, even a minimally invasive one, is estimated at 50-70%. Thoracic surgery, causes significant preoperative anxiety, especially in children. The aim of this study was to determine the effect of an important component of psychological preparation for a surgery as information support on levels of anxiety, pain and satisfaction with postoperative analgesia. Methods: The randomized double blind study including patients aged 9-18 years qualified for lateral thoracotomy or Ravitch procedure. The subjects were randomized to the control group (n=56) provided with a routine preoperative information by a nurse, and the experimental group (n=56) offered additional psychological consultation. Data were collected via the State-Trait Anxiety Inventory. Results: In the experimental group, the level of state anxiety at 48 h post-surgery was significantly lower than prior to the procedure, but only in subjects with preoperative trait anxiety Conclusion: Information support from a psychologist offered prior to a thoracic surgery decrease the level of postoperative state anxiety solely in children with lower levels of trait anxiety. Higher level of postoperative state anxiety negatively affect patients' satisfaction with post-surgical analgesia. Trial Registration: ClinicalTrials.gov; Influence of Preoperative Support on Anxiety, Pain and Satisfaction With Postoperative Analgesia; NCT03488459, https://clinicaltrials.gov/ct2/show/record/NCT03488459?cntry=PL&city=Rabka-Zdr%C3%B3j&rank=1
Keywords: anxiety; preoperative education; psychologist; thoracotomy; Ravitch procedure; postoperative pain